Amblyraja doellojuradoi, Southern Thorny Skate - Pollom, R. (2020)
The Southern Thorny Skate (Amblyraja doellojuradoi) is a small (to 69 cm total length) deepwater skate that occurs in the Southeast Atlantic Ocean from Uruguay to Southern Argentina and the Burdwood Bank, including the Falkland Islands (Malvinas). It is demersal on the mid- and outer continental shelf and upper slope at depths of 50?1,000 m. This skate is captured as bycatch in demersal trawl fisheries and possibly on longlines targeting hake, squid, and Patagonian Toothfish (Dissostichus eleginoides), and is increasingly retained for human consumption. It has some refuge at depth and is not suspected to be undergoing a reduction in population size at this time. Therefore, the Southern Thorny Skate is assessed as Least Concern.